River-lake ecosystems exhibit a strong seasonal cycle of greenhouse gas emissions - Shijie Wang; Shanghua Wu; Yuzhu Dong; Xianglong Li; Yaxin Wang; Yijing Li; Ying Zhu; Jiahui Deng; Xuliang Zhuang (Communications Earth & Environment)
Abstract Inland lakes are a crucial source of greenhouse gases, such as carbon dioxide, methane and nitrous oxide. The interconnected river-lake systems feature multiple lake regions, wherein numerous rivers interconnect various lake regions. Their intricate hydrological conditions and interactions distinguish them from conventional lakes, which typically have a single and relatively static water body. However, the greenhouse gas emission characteristics, as well as the driving forces of the interconnected river-lake systems, are still under-researched. Here, we carried out bi-seasonal in situ surveys across a typical interconnected river-lake system, Dongting Lake, along with a meta-analysis derived from 168 lakes spanning six continents, to elucidate this issue. We found that interconnected river-lake systems exhibit a unique temporal variation in carbon dioxide and nitrous oxide fluxes, with positive fluxes during the wet season but transitioning to sinks during the dry season. Greenhouse gas fluxes in conventional stable lakes are frequently correlated with abiotic factors, such as hydro-climatological conditions and trophic status. While in Dongting Lake, specific microbial species that are important to the cycling of macronutrients and other less common nutrients, alongside microbial predatory behaviour, can better predict greenhouse gas fluxes. Our study highlights the importance of biotic predictors in prospective greenhouse gases flux estimates.